ANALISIS PENGARUH KUALITAS LABA, KETERLAMBATAN PELAPORAN LABA, DAN KOMPLEKSITAS PERUSAHAAN TERHADAP ABNORMAL AUDIT DELAYS - Rizky Amalia; Rr. Sri Handayani (Diponegoro Journal of Accounting, 2019)
This research aims to examine the determinant factors of abnormal audit delays. The examined factors of this research are earnings quality, earnings report delay, and company complexity.The population of this study are manufacturing companies listed on Indonesia Stock Exchange for the period 2013-2017. Using purposive sampling method as a method of data sellecting, there are 154 total observational data. The data used in this research was secondary data. The research hypotesises were tested and analyzed using multiple regression analysis.The result of this study shows that company complexity have significant influence on abnormal audit delays. However, earnings quality and earnings report delay have no significant effect on abnormal audit delays.